EIGENVALUES AND EIGENVECTORS OF LATIN SQUARES IN MAX-PLUS ALGEBRA - Muhammad Syifa’ul Mufid; Subiono - (Journal of the Indonesian Mathematical Society, 2014)
A Latin square of order n is a square matrix with n diﬀerent numberssuch that numbers in each column and each row are distinct. Max-plus Algebra isalgebra that uses two operations, ⊕ and ⊗. In this paper, we solve the eigenproblemfor Latin squares in Max-plus Algebra by considering the permutations determinedby the numbers in the Latin squares.DOI : http://dx.doi.org/10.22342/jims.20.1.178.37-45